A Study on Convolutional Vector-Valued Neural Networks for Color Image Classification - Rodrigues, Carolina; Valle, Marcos Eduardo (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2025: Anais do XXII Encontro Nacional de Inteligência Artificial e Computacional, 2025)
Neural networks have gained significant attention in recent years since the development of deep learning. Vector-valued neural networks (V-nets), including hypercomplex-valued neural networks, are appropriate for processing multidimensional data, such as images or hyperspectral imaging. In this article, we present the mathematical foundation for the development of V-nets. We implement and apply these models for a color image classification task, specifically for detecting acute lymphoblastic leukemia in blood smear images.